COVID-19-related anxiety and lifestyle changes - Han, Song Yi; Jang, Hye Young; Ko, Young (Frontiers in Public Health, 2022)
This study aimed to identify factors that affect lifestyle changes and focused on coronavirus disease (COVID-19)-related anxiety since the COVID-19 outbreak in South Korea. Data from 213,848 individuals from the 2020 Korean Community Health Survey were analyzed using a complex sampling design. Descriptive statistics, t-tests, one-way ANOVA, and multiple regression analyses were performed. Participants reported a high level of COVID-19-related anxiety, with a score of 19.28 out of 25. The score of healthy behavioral change index was −0.51, indicating negative changes in physical activity, dietary habits, and sleep patterns. A slight positive change was reported for addictive behavioral change index, such as smoking and alcohol consumption, at 0.27 scores, indicating a decrease in these behaviors. COVID-19-related anxiety was an important factor that negatively affected health behavior. The high-risk groups that were vulnerable to anxiety included older adults and those who have little social support or few social encounters. Thus, identifying high-risk groups with the potential for worsened health behavior and providing interventions to reduce the anxiety caused by COVID-19 are necessary.